2007
DOI: 10.1021/cm062912r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Me2O3−CeO2 (Me = B, Al, Ga, In) Mixed-Oxide Catalysts

Abstract: The present work is focused on the synthesis and characterization of ceria-based mixed oxides. Ceria was combined with the other oxides from group III, with the intention of improving the catalytic properties of thus obtained materials. (B 2 O 3 , Al 2 O 3 , Ga 2 O 3 , In 2 O 3 )-CeO 2 mixed oxides with a wide range of Me 2 O 3 contents have been prepared by a coprecipitation route. The obtained solid materials have been characterized in terms of their structural, textural, and surface properties, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 67 publications
4
44
1
Order By: Relevance
“…Auroux et al systematically studied the structure, texture, surface, and redox features of CeO 2 -M 2 O 3 (M = B, Al, Ga, In) mixed oxides prepared by coprecipitation and sol-gel method, respectively. Some general conclusions had been obtained that CeO 2 -Al 2 O 3 mixed oxides exhibited the highest surface area and the presence of oxygen vacancies could be identified by Raman spectra [11,12]. Based on these above-mentioned literatures, we could find that they present the similar consideration, namely the combination of ceria with the same valance metal oxide.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Auroux et al systematically studied the structure, texture, surface, and redox features of CeO 2 -M 2 O 3 (M = B, Al, Ga, In) mixed oxides prepared by coprecipitation and sol-gel method, respectively. Some general conclusions had been obtained that CeO 2 -Al 2 O 3 mixed oxides exhibited the highest surface area and the presence of oxygen vacancies could be identified by Raman spectra [11,12]. Based on these above-mentioned literatures, we could find that they present the similar consideration, namely the combination of ceria with the same valance metal oxide.…”
Section: Introductionmentioning
confidence: 68%
“…However, it was reported that pure ceria had poor thermal stability and low specific surface area. To improve the property of ceria, many works have been performed by introducing foreign oxide, such as TiO 2 [8], ZrO 2 [9], SiO 2 [10], M 2 O 3 (M: B, Al, Ga, In) [11,12], SnO 2 [13], MnO x [14], HfO 2 [15], Co 2 O 3 [16], CaO [17], and so on. These doped ceria-based mixed oxides would cause the changes of structural, electronic, reductive, and oxygen migration properties due to doped ions incorporating into the ceria lattice to generate defects or the formation of a new phase [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, attempts were made for the size controlled preparation of cerialanthana solid solution (CLSS) assisted with cetyltrimethylammonium bromide (CTAB) and their physicochemical characterization. The adopted co-precipitation method facilitates the formation of nanoparticles with high surface area, homogenous distribution and good thermal stability [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Because of these characteristics, ceria has been widely used as a promoter in the three-way catalysts for the elimination of toxic autoexhaust gases, [4][5][6] as oxygen sensors, [7,8] as solid electrolytes in the solid oxide fuel cells, which utilizes their oxygen storage capacity, [9][10][11] as absorbents for fluoride ion or arsenic-based compounds, and as substances to filter out ultraviolet rays. [12] Cerium oxide also has a high thermal stability, displays optical behavior, electrical conductivity, and diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the synthesis of some novel CeO 2 structures, including nanorods, [15][16][17][18] nanowires, [19][20][21][22][23] nanotubes, [24,25] nanocubes, [26] microplates, [27] and other morphological structures [28][29][30][31][32][33][34][35][36] have been reported by chemical scientists. In this paper, twofold-shaped CeO 2 dendrites were successfully fabricated for the first time by thermal treatment of the cerium carbonate hydroxide precursor, which was synthesized by hydrothermal reaction of Ce(NH 4 as the cerium source is a novel route toward fabrication of CeO 2 particles; the traditional direct precipitation-decomposition route uses Ce 3+ as the cerium source. The influence of DEA on dendrite formation is discussed.…”
Section: Introductionmentioning
confidence: 99%